Catastrophization and migraine: a reflection on coping with pain - Santos, Erlene Roberta Ribeiro dos; Oliveira, Daniella Araújo de; Valença, Marcelo Moraes (Headache Medicine, 2017)
Psychological factors play an important role in the balance and control of situations that cause individual suffering, specifically those linked to pain, and are known to contribute to its aggravation. In this context, catastrophization is a set of negative thoughts in response to pain. For patients suffering from migraine, catastrophizing can generate negative reflexes for the control and coping of pain, potentiating crises. Objective: to identify the state-of-theart of scientific publication on the relationship between catastrophization and migraine. Materials and methods: This is an integrative review of literature developed from the search of papers in various databases. In LILACS, we used Portuguese descriptors of the DeCS "cefaleia", "transtornos de enxaqueca" and "catastrofização". In PubMed, SCOPUS and Web of Science, the following MeSH descriptors were uses: "headache", "Headache disorders primary", "migraine disorders" and "Catastrophization". In the CINAHL, we used DeCS descriptors "headache", "headache migraine" and "headache disorder". All categories of original papers, literature review, reflection, update, experience report, studies with individuals in the 18-50 years age group with diagnosis of migraine and symptoms of pain catastrophization were selected as eligibility criteria. Results: In a universe of 106 papers found, four that met the inclusion criteria were selected. The results of the studies show that pain catastrophization associated with migraine attacks increases the perception of the severity of migraine, contributing to feelings of inability to overcome the crisis, as well as increasing feelings of helplessness and despair that hinder pain control. Conclusion: Migraine-affected individuals that evidence pain catastrophization perceive crises in a more intense and incapacitating way, which has a negative effect and has harmful implications for their quality of life.